1992
DOI: 10.1152/jn.1992.67.5.1301
|View full text |Cite
|
Sign up to set email alerts
|

Ionic currents of morphologically distinct peptidergic neurons in defined culture

Abstract: 1. The X-organ sinus gland is a major peptidergic neurosecretory system in Crustacea, analogous to the vertebrate hypothalamoneurohypophyseal system. Neuronal somata isolated from the crab (Cardisoma carnifex) X-organ and maintained in primary culture in unconditioned, fully defined medium show immediate regenerative outgrowth. Outgrowth occurring as broad lamellipodia ("veiled") distinguishes neurons consistently showing crustacean hyperglycemic hormone immunoreactivity. Neurons that are immunoreactive agains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 0 publications
0
8
0
1
Order By: Relevance
“…To our knowledge, this is the first report of 4-AP increasing a potassium current in a cardiac preparation. In cultured peptidergic neurons from the X-organ of the crab, Meyers, Graf & Cooke (1992) found that 4-AP increased IK. They suggested that the blockade of IA in distal neurites improved voltage control and recruited additional conductance from distal regions of the membrane.…”
Section: R a Navarro-polanco And J A Stnchez-chapulamentioning
confidence: 92%
“…To our knowledge, this is the first report of 4-AP increasing a potassium current in a cardiac preparation. In cultured peptidergic neurons from the X-organ of the crab, Meyers, Graf & Cooke (1992) found that 4-AP increased IK. They suggested that the blockade of IA in distal neurites improved voltage control and recruited additional conductance from distal regions of the membrane.…”
Section: R a Navarro-polanco And J A Stnchez-chapulamentioning
confidence: 92%
“…Outward potassium currents of neurons were examined with a bath saline containing both TTX and Cd 2+ to eliminate possible competing inward Na + and Ca 2+ currents (Meyers et al, 1992;Richmond et al, 1995). Two subtypes of K + currents, transient outward current (I A ) and delayed rectifier current (I K ), were recorded with a series graded concentrations of PFOS applications.…”
Section: Effect Of Pfos On Voltage-dependent Potassium Channel Currentsmentioning
confidence: 99%
“…Dispersed XO cells have been cultured in vitro, where they show axonal outgrowth and the development of elaborate branching and lamellipodial morphologies. Electrophysiological and morphological studies (e.g., on neurosecretory granule content) have been performed on such cells in culture (Cooke et al 1989;Grau and Cooke 1992;Meyers et al 1992), and LG lamina ganglionaris ; ME, MI, MT medullae externa, interna, and terminalis; SG sinus gland; XO X-organ. Bars b, c 50 urn; inset 10 urn.…”
Section: Introductionmentioning
confidence: 99%